Analyzing the elements of Naguib Mahfouzâs short stories: The example of âThe Infamous Houseâ - Payman salehi (دراسات في اللغة العربيّة وآدابها)
One of the most important reasons for the success of literary figure is his sufficient use of story elements such as characterization, plot, point of view, symbols. This study critically analyses the different literary elements in Naguib Mahfouz’s famous collection of short stories, “The Infamous House” consisting of 18 stories.  At first, we offer a definition of the short story as a genre and consider why Naguib Mahfouz worked on short stories; then, having introduced the short stories in the collection, we subject them to criticism. It is revealed that most of the stories begin with the introduction of the main character. In some of them before meeting the character, the readers encounter the main conflict of the story. Doing this prevents the story from boring the readers. One of the positive points of the early stories is that their length match their plots. Apart from “Ashes” which has the first person point of view, other stories are narrated through an omniscient point of view. In the later stories, which include psychological analyses of the characters, the description of their physical appearance is briefer and more technical; so it is not the narrator that tells the appearance of the people; most of the descriptions are done by other characters. Some features of his prose include using exclamatory sentences, beautiful metaphors, proverbs, and irony.